The Influence of Vertical Distance of Tie Beams in Building Substructures on Structural Response and Soil Behavior - Rico Daniel Sumendap; Dody M.J. Sumajouw; Fabian J. Manoppo (Journal of Engineering, Electrical and Informatics, 2025)
Indonesia, located in a high seismic zone, requires building structures to be designed with strong earthquake resilience. Tie beams are commonly used in pile foundation systems to improve substructure stability, yet their vertical positioning is rarely analyzed in relation to overall building performance. This study investigates the influence of vertical distance of tie beams in reinforced concrete substructures on both structural response and soil behavior under seismic loading. A seven-story educational building was modeled using SAP2000 with varying tie beam elevations (−1.30 m to 0.00 m). Structural parameters analyzed included inter-story displacement, drift ratio, and stability index (θ), while subsoil behavior was evaluated through soil displacement in X, Y, and Z directions. The results showed that placing the tie beam at 0.00 m significantly reduced structural drift and improved overall stability. Meanwhile, the smallest soil displacement in the X and Z directions occurred when tie beams were placed at −1.00 m. However, in the Y direction, tie beams at 0.00 m produced slightly higher soil movement than configurations without tie beams. These findings highlight the importance of vertical tie beam placement in optimizing both structural and geotechnical performance in seismic design.